Automated Analysis of Nano‐Impact Single‐Entity Electrochemistry Signals Using Unsupervised Machine Learning and Template Matching - Ziwen Zhao; Arunava Naha; Sagar Ganguli; Alina Sekretareva (Advanced Intelligent Systems, 2024)
Nano‐impact (NIE) (also referred to as collision) single‐entity electrochemistry is an emerging technique that enables electrochemical investigation of individual entities, ranging from metal nanoparticles to single cells and biomolecules. To obtain meaningful information from NIE experiments, analysis and feature extraction on large datasets are necessary. Herein, a method is developed for the automated analysis of NIE data based on unsupervised machine learning and template matching approaches. Template matching not only facilitates downstream processing of the NIE data but also provides a more accurate analysis of the NIE signal characteristics and variations that are difficult to discern with conventional data analysis techniques, such as the height threshold method. The developed algorithm enables fast automated processing of large experimental datasets recorded with different systems, requiring minimal human intervention and thereby eliminating human bias in data analysis. As a result, it improves the standardization of data processing and NIE signal interpretation across various experiments and applications.